ANALYSIS OF THE IMPLEMENTATION OF PANCASILA STUDENT PROFILE IN THE DIMENSION OF GOTONG ROYALONG GRADE V AT STATE ELEMENTARY SCHOOL 1 LAMBHEU ACEH BESAR - Ramadha, Azura Shari; Nurmasyitah, Nurmasyitah; Tursinawati, Tursinawati (Universitas Syiah Kuala, 2024)
In the Pancasila student profile there are six personality values, one of which is mutual cooperation. Gotong royong as a Pancasila student profile guides students to become human beings who have social values and attitudes that make it easier to socialize by helping each other. At SDN 1 Lambheu, the school has started implementing the Pancasila student profile, although it has not yet been fully implemented. The problem in this research is